SYNTHESIS OF SILVER NANOPARTICLES AND ANTIMICROBIAL ACTIVITIES OF METHANOLIC EXTRACT OF AZADIRACHTA INDICA LEAF AGAINST ESCHERICHIA COLI, STAPHYLOCOCCUS AUREUS AND CANDIDA ALBICANS - Agbaje, AbdulGaniy; Muhammed, Maryam Moyosore; Bello, Sharafa Adegoke; Jimoh-Hamza, Oluwabukola Kudirat; Kazeem, Muinat Olanike; Azeez, Zainab Oluwatoyin; Jibril, Khadijat Ndagi (FUDMA JOURNAL OF SCIENCES, 2023)
Azadirachta indica is a plant commonly known as neem. It is native to the Indian subcontinent and most countries in Africa, including Nigeria. The aim of this study was to synthesise silver nanoparticles and examine antimicrobial activities of crude methanolic extract of Azadirachta indica leaves on clinical isolates of Staphylococcus aureus, Escherichia coli and Candida albicans. Methanol was the solvent used for the extraction. The characterization of synthesized AgNPs was carried out using the UV-Visible spectrophotometer. Antimicrobial activity was conducted using disc diffusion method while the Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and Minimum Fungicidal Concentration (MFC) were determined using broth dilution method. The antimicrobial activity of the synthesized Azadirachta indica AgNPs was carried out using standard agar well diffusion method. Qualitative phytochemicals analysis revealed presence of tannins, phenols, alkaloids, phytosteroid, and terpenoid while flavonoids, steroids and saponin were absent. Antibacterial activities of the extracts using the ditch method (concentrations of 100mg/mL, 50mg/mL, 25mg/mL, 12.5mg/mL, and 6.25mg/mL) recorded no zone of inhibition for Staphylococcus aureus and Escherichia coli. Antimicrobial activity of synthesized silver nanoparticles (AgNPs) from methanolic extract showed no zone of inhibition for Staphylococcus aureus. The zone of inhibition against Escherichia coli was 5.33mm while for Candida albicans the zone of inhibition was 15.33mm. Based on the results obtained from this study, it could be said that methanolic extract of Azadirachta indica leaves contains phytochemicals of pharmacological significance which could be exploited as antifungal agent.